Calcium modulates interactions between bacteria and hydroxyapatite - Venegas, Susana Carolina (2006)
Bacterial adhesion onto hydroxyapatite is known to depend on the surface properties of both the biomaterial and the bacterial strain, but less is known about the influence of the composition of the aqueous medium. Here, the adhesion of Streptococcus mutans and 3 different Lactobacilli on powdered hydroxyapatite was shown to change with Ca 2+ concentration. The effect depends on the surface properties of each strain. Adhesion of Lactobacillus fermentum and salivarius (and of Streptococcus mutans at low Ca 2+) was enhanced with increasing Ca 2+ concentration. Lactobacillus casei was efficiently removed by adhesion on hydroxyapatite, even without Ca 2+ addition, and the effect of this ion was only marginal. The results are interpreted in terms of Ca 2+-mediated adhesion, and relative to the hydrophobic properties of each strain and the electrical properties of the bacterial and solid surfaces (electrophoretic mobility).